PROJECT SCHEDULING ANALYSIS USING CPM AND PERT IN THE CONSTRUCTION OF NAKULA SHOP HOUSES - Ade Yuri Syaban Ramadhan; Caroline Taruliasih Manik; Santi Dwi Zulfa; Ahmad Zarwantoni; Ni Ketut Tari Tastrawati (Adisam Publisher, 2025)
The success of a project is often caused by the lack of planning and control of a project that is less effective, therefore project completion often experiences delays and costs are increasing. In the practice, the duration of project completion is limited in accordance with the mutually agreed upon agreement so that it is necessary to anticipate changes in conditions that will occur. Project management is needed to manage projects to be more optimal by utilizing CPM and PERT. By comparing CPM (Critical Path Method) and PERT (Project Evaluation and Review Technique) in project scheduling on the construction of Ruko Nakula carried out by PT Artha Wijaya Utama, CPM has a faster project completion duration than PERT. The duration required to finish a project with CPM is 49 weeks while PERT requires a duration of 52 weeks.